Question
4. If \( \tan 22^{\circ}=t \) write the following in terms of \( t \). \( \begin{array}{ll}\text { (a) } \tan 202^{\circ} & \text { (b) } \tan 338^{\circ}\end{array} \)
Ask by Hall Simpson. in South Africa
Feb 04,2025
Real Tutor Solution
Tutor-Verified Answer
Answer
\( \tan 202^{\circ} = t \) and \( \tan 338^{\circ} = -t \).
Solution
To express \( \tan 202^{\circ} \) and \( \tan 338^{\circ} \) in terms of \( t = \tan 22^{\circ} \), we'll use the periodic and symmetry properties of the tangent function.
### (a) \( \tan 202^{\circ} \)
**Step 1: Express 202° in terms of 180° and 22°**
\[
202^{\circ} = 180^{\circ} + 22^{\circ}
\]
**Step 2: Use the periodicity of tangent**
The tangent function has a period of 180°, meaning:
\[
\tan(\theta + 180^{\circ}) = \tan \theta
\]
**Applying this:**
\[
\tan 202^{\circ} = \tan(180^{\circ} + 22^{\circ}) = \tan 22^{\circ} = t
\]
### (b) \( \tan 338^{\circ} \)
**Step 1: Express 338° in terms of 360° and 22°**
\[
338^{\circ} = 360^{\circ} - 22^{\circ}
\]
**Step 2: Use the symmetry of tangent**
The tangent function has the property:
\[
\tan(360^{\circ} - \theta) = -\tan \theta
\]
**Applying this:**
\[
\tan 338^{\circ} = \tan(360^{\circ} - 22^{\circ}) = -\tan 22^{\circ} = -t
\]
### **Final Answers:**
- **(a)** \( \tan 202^{\circ} = t \)
- **(b)** \( \tan 338^{\circ} = -t \)
Reviewed and approved by the UpStudy tutoring team
Like
error msg
Explain
Simplify this solution
The Deep Dive
To solve for \( \tan 202^{\circ} \) and \( \tan 338^{\circ} \) in terms of \( t \), where \( t = \tan 22^{\circ} \), we can utilize the properties of tangent and the periodicity of the tangent function. For \( \tan 202^{\circ} \): \[ \tan 202^{\circ} = \tan(180^{\circ} + 22^{\circ}) = \tan 22^{\circ} = t. \] For \( \tan 338^{\circ} \): \[ \tan 338^{\circ} = \tan(360^{\circ} - 22^{\circ}) = -\tan 22^{\circ} = -t. \] Thus, we can express the solutions as: \[ \text{(a)} \tan 202^{\circ} = t, \quad \text{(b)} \tan 338^{\circ} = -t. \]